The Economic impact of shrimp sector exports in Ecuador - Cedeño Quinto, Jenny; Ulloa Noboa, Lotty; Claro Pérez, Pedro (International Journal of Studies in Administrative Sciences STRATEGOS, 2026)
This study focused on analyzing the economic impact of the shrimp farming sector in Ecuador during the period 2020–2024, based on the premise that this industry has consolidated itself as one of the country’s main drivers of non-oil exports, even in a context marked by price volatility, trade dependence, and climate pressures. With this in mind, the study’s main objective was to examine the evolution of production, exports, prices, economic contribution, employment, and the factors that influenced the sector’s profitability. The research methodology employed a mixed-methods approach, primarily documentary in nature, with a descriptive, non-experimental, and exploratory design. This approach was based on the review and analysis of secondary information from official sources, technical reports, and specialized literature. Specifically, a descriptive approach was used to compare trends and annual variations. The main findings showed sustained growth in shrimp production and its share of non-oil exports, but also revealed a decline in profitability starting in 2023 due to lower international prices, increased production costs, and the persistent concentration of sales in the Chinese market. The study also determined that the sector generated a moderate increase in employment and contributed to regional economic growth, although progress varied across provinces. Finally, it concluded that the sector’s competitiveness depended on both its production capacity and its resilience to external risks, highlighting the need to diversify markets, optimize costs, and strengthen climate adaptation strategies. Indeed, this study provided a comprehensive overview of the sector’s economic performance and identified priority areas for further research.